2018
DOI: 10.1111/codi.13973
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between 18F‐FDGPETCT‐derived markers of tumour metabolism and systemic inflammation in patients with recurrent disease following surgery for colorectal cancer

Abstract: The present study reports a direct association between F-FDG-PETCT-derived measures of tumour metabolism and systemic inflammation in patients with recurrent colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…A recent study conducted in 73 advanced HNSCC patients (Ohashi et al 2020 ) proved that WBC count was significantly correlated with 18 F-FDG PET/CT parameters, and speculated that tumor with upregulated aerobic glycolysis produce large amounts of lactic acid and cytokines and might mediate systemic inflammation via the lactic acid-induced IL-23/IL-17 pathway. Several studies also confirmed the relationship between PET-CT volumetric metabolic parameters and NLR/PLR in SCLC, NSCLC, cervical carcinoma and colorectal cancer (Du et al 2019 ; McSorley et al 2018 ; Mirili et al 2019 ; Wang et al 2020 ).…”
Section: Discussionmentioning
confidence: 77%
“…A recent study conducted in 73 advanced HNSCC patients (Ohashi et al 2020 ) proved that WBC count was significantly correlated with 18 F-FDG PET/CT parameters, and speculated that tumor with upregulated aerobic glycolysis produce large amounts of lactic acid and cytokines and might mediate systemic inflammation via the lactic acid-induced IL-23/IL-17 pathway. Several studies also confirmed the relationship between PET-CT volumetric metabolic parameters and NLR/PLR in SCLC, NSCLC, cervical carcinoma and colorectal cancer (Du et al 2019 ; McSorley et al 2018 ; Mirili et al 2019 ; Wang et al 2020 ).…”
Section: Discussionmentioning
confidence: 77%
“…In addition, the circulating neutrophils could act as a surrogate for tumor-associated neutrophils, which act as adhesive adapters between circulating tumor cells and the metastatic target and play an important role in tumor angiogenesis and growth by secreting vascular endothelial growth factor and matrix metalloproteinase [15,17]. On the other hand, lymphocytes possess an anti-tumor effect by inducing tumor cell apoptosis and mediating antibody-dependent cell-mediated cytotoxicity [22][23][24]. Moreover, memory T-cells are considered to have a crucial role in carcinogenesis [25].…”
Section: Discussionmentioning
confidence: 99%
“…The remaining 10 articles had their bibliographies reviewed in a systematic manner. This identified a further 2 articles to be included in the final analysis, leading to final figure of 12 articles considered in the present systematic review (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31).…”
Section: Study Selection Processmentioning
confidence: 99%